Profile of Microbial Keratitis at a Referral Center in Iraq - Al-Shakarchi, Faiz I; Hussein, Marwa A; Al-Shaibani, Abdulwahid B (Al-Nahrain Journal of Science, 2018)
One hundred and five (105) corneal scraping samples were taken from patients suffering of microbial keratitis referred to Ibn Al-Haitham Eye Teaching Hospital in Baghdad. After culturing on the related selective media, results showed that 73 of the samples were positive for occurrence of microorganisms; of these, 68 (64.76%) were belonged to bacterial and 5 (6.85%) to fungi. After the bacterial isolates were identified by cultural, microscopic and biochemical examinations, the following species and percentages were recorded: Pseudomonas aeruginosa 29 (39.73%), Staphylococcus aureus 22 (30.14%) and Staphylococcus epidermidis 17 (23.28%). While the fungal isolates were belonged to Aspergillus niger 3 (4.12 %) and Alternaria spp. 2 (2.73 %) according to their identification through the cultural and microscopic examinations, in addition to the types and shapes of fungal spores. Upon such findings, P.aeruginosa was the predominant bacteria and A.niger the prevalent fungi. Regarding to the patients gender, it was found that cases of microbial keratitis in the samples were more abundant in males 41 (56.16%) than in females 32 (42.85%). Patients group of age (41-59) years was the most microbial keratitis infected group with a percentage of (30.20 %), while the lowest infected group was (≥ 60) year with a percentage of (17.80 %).